2018
DOI: 10.1093/mnras/sty3051
|View full text |Cite
|
Sign up to set email alerts
|

A panchromatic spatially resolved study of the inner 500 pc of NGC 1052 – I. Stellar population

Abstract: We map optical and near-infrared (NIR) stellar population properties of the inner 320×535 pc 2 of the elliptical galaxy NGC 1052. The optical and NIR spectra were obtained using the Gemini Integral Field Units of the GMOS instrument and NIFS, respectively. By performing stellar population synthesis in the optical alone, we find that this region of the galaxy is dominated by old (t>10 Gyr) stellar populations. Using the NIR, we find the nucleus to be dominated by old stellar populations, and a circumnuclear rin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 76 publications
(115 reference statements)
1
11
0
Order By: Relevance
“…3.3.1). The presence of this component has been previously reported by Dahmer-Hahn et al (2019b) but only in [O III] with FWHM ∼ 1380 km s −1 . These authors propose that is tracing the interaction between the jet and the ISM-environment.…”
Section: Multi-phase Ism Propertiessupporting
confidence: 58%
See 1 more Smart Citation
“…3.3.1). The presence of this component has been previously reported by Dahmer-Hahn et al (2019b) but only in [O III] with FWHM ∼ 1380 km s −1 . These authors propose that is tracing the interaction between the jet and the ISM-environment.…”
Section: Multi-phase Ism Propertiessupporting
confidence: 58%
“…For NGC 1052, the presence of non rotational motions such as an AGN-driven outflow has been suggested in many previous works on the basis of HST imaging (Pogge et al 2000;Walsh et al 2008) as well as 1D and IFS spectroscopy (Sugai et al 2005;Dopita et al 2015;Cazzoli et al 2018;Dahmer-Hahn et al 2019b), mostly in the optical band.…”
Section: The Intriguing Ism Kinematics In Ngc 1052mentioning
confidence: 85%
“…To date 20 papers showing specific analyses of DIVING 3D data have already been published. Studies (focused on the line-emitting regions, the stellar and gas kinematics and the stellar archaeology) of the central regions of six individual galaxies of the DIVING 3D sample resulted in the following publications: NGC 4594 (Menezes et al 2013), NGC 1313 , NGC 5044 (Diniz et al 2017), NGC 7582 (Ricci et al 2018), NGC 1052(Dahmer-Hahn et al 2019a and NGC 2835 (Menezes et al 2019). In certain objects, peculiar features were detected, such as an off-centred AGN in NGC 3115 (Menezes et al 2014b), a compact off-centred Seyfert emission (with a deficit of emission at the AGN position) in NGC 3621 (Menezes et al 2016), double stellar nuclei in NGC 908 and NGC 1187 ) and a double-peaked H𝛼 emission in NGC 4958 .…”
Section: Early Resultsmentioning
confidence: 99%
“…Previous studies of individual AGN hosts in the NIR, on the other hand, found rings of stellar populations with ages between 0.1 and 2.0 Gyr (e.g. Riffel et al 2010Storchi-Bergmann et al 2012;Schönell et al 2017;Dahmer-Hahn et al 2019;Diniz et al 2019). The authors also found that these regions are usually associated with rings of lower stellar 𝜎, suggesting that the intermediateage stellar populations were formed from low-velocity dispersion gas.…”
Section: Introductionmentioning
confidence: 93%